2014
DOI: 10.2355/isijinternational.54.926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempering Temperature on the Microstructure and Hardness of a Super-bainitic Steel Containing Co and Al

Abstract: The effect of tempering temperature, within the range of 400 to 700°C, on the microstructure and hardness of two super-bainitic steels, one as the control parent sample and the other with added Co & Al was investigated. Post-tempering examinations of the super-bainitic samples showed that low temperature tempering cycles (400-500°C) resulted in carbides formation, and some increases in the hardness possibly due to precipitation strengthening in the Co & Al contained steel. Once the tempering temperature increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In essence, the microstructure of BM and SCHAZ is tempered martensite, while the tempering temperature and the endurance of tempering are different between BM and SCHAZ. Many research showed that the hardness decreases with tempering temperature overall [31]. From point D to point E, the magnitude of hardness increases due to the weakening tempering effect back to the level of the base material.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the microstructure of BM and SCHAZ is tempered martensite, while the tempering temperature and the endurance of tempering are different between BM and SCHAZ. Many research showed that the hardness decreases with tempering temperature overall [31]. From point D to point E, the magnitude of hardness increases due to the weakening tempering effect back to the level of the base material.…”
Section: Discussionmentioning
confidence: 99%
“…Then, at higher tempering temperatures, a hardness drop was revealed, and at 650 • C, the hardness was 418 ± 5 HV1. In contrast, many investigations indicate a continuous decrease in the hardness of bainitic steels [27,[49][50][51]. Based on the microstructural approach (Figure 14), designed steel during the tempering processes was characterized by a comparable morphology of structure up to a temperature of 500 °C (not presented here) in relation to the austempering process (Figure 14a).…”
Section: Tempering Process-thermal Stability Evaluationmentioning
confidence: 99%